2004
DOI: 10.1037/0022-006x.72.4.660
|View full text |Cite
|
Sign up to set email alerts
|

Couples' Support-Related Communication, Psychological Distress, and Relationship Satisfaction Among Women With Early Stage Breast Cancer.

Abstract: This study examined associations between couple communication about cancer and psychological distress and relationship satisfaction of women diagnosed with early stage breast cancer. One hundred forty-eight couples completed a videotaped discussion of a cancer-related issue and a general issue. Patients completed measures of psychological distress and relationship satisfaction. Videotapes were coded with the Rapid Marital Interaction Coding System. Analyses focused on partner responses to patient self-disclosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 36 publications
13
149
3
5
Order By: Relevance
“…Partners are required to support their spouses in their daily lives, to accompany them during treatments and examinations, to take greater responsibility for their home and children, all of which can lead to psychosocial problems (Given et al, 1992;Compas et al, 1994). In several studies, it was found that the partners themselves often experienced higher levels of distress than the cancer patient, and that there is a high concordance between the distress levels of the patient and the partner (Manne et al, 2004;Segrin et al, 2007;Yusoff et al, 2011). The aim of the present study therefore was to investigate anxiety, depression and sexual satisfaction levels of Turkish breast cancer patients and also their partners.…”
Section: Introductionmentioning
confidence: 99%
“…Partners are required to support their spouses in their daily lives, to accompany them during treatments and examinations, to take greater responsibility for their home and children, all of which can lead to psychosocial problems (Given et al, 1992;Compas et al, 1994). In several studies, it was found that the partners themselves often experienced higher levels of distress than the cancer patient, and that there is a high concordance between the distress levels of the patient and the partner (Manne et al, 2004;Segrin et al, 2007;Yusoff et al, 2011). The aim of the present study therefore was to investigate anxiety, depression and sexual satisfaction levels of Turkish breast cancer patients and also their partners.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, disclosing one's emotions and thoughts concerning a cancer experience may be different from disclosing emotions and thoughts concerning other personal events, especially acute events such as an upsetting movie. These issues were addressed by Manne, Ostroff, Sherman, et al (2004), who made use of observational data from women with breast cancer and their male partners. The degree of self-disclosures during a cancer-related discussion was not associated with the women's psychological distress as assessed a few days before the discussion.…”
Section: Mutual Self-disclosurementioning
confidence: 99%
“…This dyadic perspective should be reflected when conceptualizing the research question, choosing a study design, selecting methodology and measures, and by using dyadic-level statistical approaches to analyze and interpret the data. [134][135][136] Second, it will be important to use multimethod approaches to measure marital processes by including observational 137 and daily diary methods 138 that can capture the interactional nature of these processes. Measures of some relationship-enhancement behaviors, such as relationship awareness, need to be developed and validated for the cancer context.…”
Section: Directions For Future Researchmentioning
confidence: 99%